BCG-mediated protection against Mycobacterium ulcerans infection in the mouse. - Paul J Converse; Deepak V Almeida; Eric L Nuermberger; Jacques H Grosset (Public Library of Science (PLoS), 2011)
Vaccination with Mycobacterium bovis bacille Calmette-Guérin (BCG) is widely used to reduce the risk of childhood tuberculosis and has been reported to have efficacy against two other mycobacterial diseases, leprosy and Buruli ulcer caused by M. ulcerans (Mu). Studies in experimental models have also shown some efficacy against infection caused by Mu. In mice, most studies use the C57BL/6 strain that is known to develop good cell-mediated protective immunity. We hypothesized that there may be differences in vaccination efficacy between C57BL/6 and the less resistant BALB/c strain.We evaluated BCG vaccine efficacy against challenge with ∼3×10(5)M. ulcerans in the right hind footpad using three strains: initially, the Australian type strain, designated Mu1617, then, a Malaysian strain, Mu1615, and a recent Ghanaian isolate, Mu1059. The latter two strains both produce mycolactone while the Australian strain has lost that capacity. CFU of both BCG and Mu and splenocyte cytokine production were determined at intervals after infection. Time to footpad swelling was assessed weekly.BCG injection induced visible scars in 95.5% of BALB/c mice but only 43.4% of C57BL/6 mice. BCG persisted at higher levels in spleens of BALB/c than C57BL/6 mice. Vaccination delayed swelling and reduced Mu CFU in BALB/c mice, regardless of challenge strain. However, vaccination was only protective against Mu1615 and Mu1617 in C57BL/6 mice. Possible correlates of the better protection of BALB/c mice included 1) the near universal development of BCG scars in these mice compared to less frequent and smaller scars observed in C57BL/6 mice and 2) the induction of sustained cytokine, e.g., IL17, production as detected in the spleens of BALB/c mice whereas cytokine production was significantly reduced, e.g., IL17, or transient, e.g., Ifnγ, in the spleens of C57BL/6 mice.The efficacy of BCG against M. ulcerans, in particular, and possibly mycobacteria in general, may vary due to differences in both host and pathogen.